Relasi Hukum Islam dan Adat dalam Tradisi Pamogih pada Perkawinan Masyarakat Muslim Bondowoso - Ali Akhbar Abaib Mas Rabbani Lubis; Muhammad Abdul Khaliq Suhri (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This study aims to discusses pamogih tradition in Bondowoso Muslim community marriages. Pamogih tradition is basically similar to ben-giben, seserahan, pasrahan tukon, uang japuik, and others. In addition to the uniqueness of the term, this research also involves legal procession and consequences. This research uses qualitative methods and fieldwork clusters. The result shows that pamogih tradition is the bridegroom obligation to give handover as a form of tradition including necklaces, rings, clothes and other household furniture as agreed by both parties. The gift is considered to have a magical value for the people. Usually, this practice is carried out before and after the marriage covenant, generally the provision of goods is done after the marriage covenant. The pamogih tradition is carried out according to the rules of ponggebeh as an elder. The legal consequences of this tradition is, if the bridegroom violates or does not carry out this tradition, it is believed that they might have bad luck experience and slander as well as exclusion from the community. The pamogih tradition is part of living law as a social phenomenon that makes this tradition as an adat law and its implementation is integrated with the practice of marriage in Islam.